Antibacterial Potential of Bajakah Tampala Root Extract (Spatholobus littoralis Hassk.) Against the Growth of Staphylococcus aureus - Nesa Putri Candra Cahyani; Iwan Sahrial Hamid; Epy Muhammad Luqman; Maya Nurwartanti Yunita; Ratih Novita Praja (Journal of Basic Medical Veterinary, 2026)
Staphylococcus aureus infections remain a significant problem in human and veterinary medicine, particularly due to the increasing prevalence of antibiotic resistance. The use of natural materials as alternative antibacterial agents is a potential solution. This study aimed to determine the antibacterial activity of bajakah tampala root extract (Spatholobus littoralis Hassk.) against the growth of Staphylococcus aureus in vitro. This study was a laboratory experimental study using a post-test-only control group design. Bajakah tampala root extract (Spatholobus littoralis Hassk.) was prepared at concentrations of 25%, 50%, 75%, and 100%. Antibacterial activity was evaluated using the disc diffusion method on Mueller–Hinton Agar (MHA). Erythromycin was used as a positive control. The observed parameter was the diameter of the inhibition zone after 24 hours of incubation at 37°C. Data were analyzed using a one-way ANOVA test. The results showed that bajakah tampala root extract (Spatholobus littoralis Hassk.) inhibited the growth of Staphylococcus aureus at all tested concentrations. The diameter of the inhibition zone increased with increasing extract concentration, with the 100% concentration producing the greatest inhibition. Statistical analysis showed a significant difference between the treatment groups and the control (p < 0.05).